Hidden blood loss between percutaneous pedicle screw fixation and the mini-open Wiltse approach with pedicle screw fixation for neurologically intact thoracolumbar fractures: a retrospective study - Haitao Jiang; Wenbo Sheng; Hantao Yuan; Jianhua Xu; Xiaochun Chen; Xiaohua Gu; Sibo Li (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background The aim of this study was to determine the proportion of hidden blood loss (HBL) in patients treated with minimally invasive surgery, and to compare the HBL between patients treated with percutaneous pedicle screw fixation (PPSF) and the mini-open Wiltse approach with pedicle screw fixation (MWPSF). Methods From January 2017 to January 2019, a total of 119 patients with thoracolumbar fractures were included in the analysis, of which 58 cases received PPSF and 61 cases received MWPSF. The clinical information and demographic results were collected and compared. And the HBL of the patients is calculated by the combination formulas of Nadler, Gross and Sehat. Results Compared with the PPSF group, operation time of MWPSF is shorter. The fluoroscopy times are 13.6 ± 3.0 in PPSF group and 5.6 ± 1.6 in MWPSF group (p < 0.001). As shown in Table 3, the intraoperative blood loss in PPSF group is 31.9 ± 9.6 ml, which is significantly less than that in the MWPSF group (44.0 ± 14.9 ml). The HBL (445.7 ± 228.9 ml), and HBL% (91.2 ± 7.7%) of the PPSF group are significantly higher than that in the MWPSF group (P < 0.05). And the total blood loss (TBL) of the PPSF group (477.6 ± 228.8 ml) is also more than that in the MWPSF group (401.0 ± 171.3 ml). Conclusions Our results suggest that in the minimally invasive surgical treatment of thoracolumbar fractures, the perioperative HBL is much higher than visible blood loss (VBL). Although PPSF has less intraoperative blood loss, it has higher TBL and HBL than those of MWPSF. Compared with MWPSF, we should pay more attention to the postoperative anemia status of patients with thoracolumbar fractures undergoing PPSF surgery.